3D Particle‐Free Printing of Biocompatible Conductive Hydrogel Platforms for Neuron Growth and Electrophysiological Recording. (27th January 2021) - Wang, Chen; Rubakhin, Stanislav S.; Enright, Michael J.; Sweedler, Jonathan V.; Nuzzo, Ralph G.
Abstract: Electrically conductive 3D periodic microscaffolds are fabricated using a particle‐free direct ink writing approach for use as neuronal growth and electrophysiological recording platforms. A poly (2‐hydroxyethyl methacrylate)/pyrrole ink, followed by chemical in situ polymerization of pyrrole, enables hydrogel printing through nozzles as small as 1 µ m. These conductive hydrogels can pattern complex 2D and 3D structures and have good biocompatibility with test cell cultures (≈ 94.5% viability after 7 days). Hydrogel arrays promote extensive neurite outgrowth of cultured Aplysia californica pedal ganglion neurons. This platform allows extracellular electrophysiological recording of steady‐state and stimulated electrical neuronal activities. In summation, this 3D conductive ink printing process enables the preparation of biocompatible and micron‐sized structures to create customized in vitro electrophysiological recording platforms. Abstract : A particle‐free direct ink writing approach is developed for the preparation of electrically conductive, biocompatible hydrogels. With newly achievable micron‐scale resolution printing, 3D periodic microscaffolds are obtained to create customized neuron recording platforms for in vitro probing of steady‐state and stimulated electrical neuronal activities.